Financial Literacy and Inclusion in Msme Management Towards Financial Freedom and Economic Inclusivity in Sampit - Herzalina Herbenita, M.M.; Lina Aprililiani, S.M., M.Ak (Keizai, 2026)
This study examines how financial literacy and financial inclusion contribute to improving financial management practices among MSME actors in Sampit City, particularly in their efforts to achieve financial independence as the foundation for a more inclusive local economy. The research adopts a quantitative approach with descriptive and associative designs, while respondents are selected using purposive sampling. A total of 65 active MSME participants were involved, responding to a questionnaire developed based on objective-based measurement. The data were analyzed using descriptive statistics and multiple linear regression with the support of SPSS. The findings reveal that financial literacy has a positive and significant effect on the quality of MSME financial management. Around 72% of respondents demonstrate a high level of financial literacy, especially in bookkeeping, risk management, and the utilization of financial products such as KUR. Financial inclusion also shows a positive influence, reflected in the high share of business account ownership (74%) and the use of digital payment services (62%). These two aspects help MSMEs manage cash flow more effectively, plan business needs, and strengthen their financial independence. Overall, the study reinforces that enhancing financial literacy and financial inclusion is a crucial step in accelerating Financial Freedom for MSMEs while promoting a more inclusive economic environment in Sampit City. The results align with national development priorities and support government programs that emphasize MSME transformation through digitalization and expanded access to formal financial services